Beitrag zur Kenntnis des Männchens der Grünen Kaffeeschildlaus, Coccus viridis (Green) (Hemiptera: Coccinea - Coccidae). - Köhler, Günter (Contributions to Entomology = Beiträge zur Entomologie, 1976)
The male of Coccus viridis (Green) was discovered on Java by Keuchenius (1915) and briefly described. This paper presents a more detailed description of pronymph, nymph and imago and some body measurements of the adult male. The cycle of development, duration of development and life-span of the male coccid were examined. The results of field studies indicated relations between the frequency of males and the density of population.